Grain size effect of pre‐ and post‐coating treated cemented carbides on PVD films' adhesion and mechanical properties. Issue 8 (19th August 2013) - Bouzakis, K.‐D.; Michailidis, N.; Skordaris, G.; Tsouknidas, A.; Makrimallakis, S.; Bouzakis, E.
Abstract The grain size of coated cemented carbide tools may significantly affect the tool life by influencing either the coating adhesion to the substrate or the coating growth during deposition. In the present study three variously grained cemented carbides were coated with two different PVD films. Various pre‐ and post‐treatments were applied, while their effect on the films' mechanical properties and adhesion was assessed by nanoindentations and inclined impact tests. The coatings deposited on ultra‐fine‐grained substrates exhibited the highest mechanical properties overall. The research revealed elevated adhesive properties for the fine‐grained substrate compared to the normal and ultra‐fine‐grained one. The film adhesion of normal and fine‐grained substrate can be further enhanced through micro‐blasting. Post‐treatments of the coatings were beneficial in all substrate cases, as brushing of the film surface removed droplets while at the same time inducing surface residual stresses at the coating resulting in a hardness increase.